Police Matters : The Everyday State and Caste Politics in South India, 1900–1975 - Kumar, Radha, 1981- (Book collections on Project MUSE., 2021)
"A history of the entwinement of everyday police and caste authority in the colonial and postcolonial Tamil countryside in twentieth-century south India"--